Immunogenicity and efficacy of serogroup A and D bacterins against Pasteurella multocida in mice - Guan, Li-jun; Yang, Jin-qian; Xu, Qing-yuan; Feng, Yi-fan; Zhang, Xi-chen; Tang, Bo; Zhao, Zhan-qin (Frontiers in Veterinary Science, 2023)
Introduction Pasteurella multocida is a widespread respiratory pathogen in pigs, causing swine pneumonia and atrophic rhinitis, and the capsular serogroups A and D are the main epidemic serogroups in infected animals. This study investigated the protective effects of serogroup A and D bacterins against current circulating P. multocida strains, to better understand the immunity generated by bacterins. Method 13 serogroup A (seven A: L3 and six A: L6 strains) and 13 serogroup D (all D: L6 strains) P. multocida strains were isolated, and used as inactivated whole cell antigen to prepare P. multocida bacterins. Mice were immunized with these bacterins at 21-day interval and intraperitoneally challenged with the homologous and heterologous P. multocida strains, respectively. The antibody titer levels and immunization protective efficacy of vaccines were evaluated. Results All of the bacterins tested induced high titer levels of immunoglobulin G antibodies against the parental bacterial antigen in mice. Vaccination with the six A: L6 bacterins provided no protection against the parent strain, but some strains did provide heterologous protection against A: L3 strains. Vaccination with the seven A: L3 bacterins provided 50%–100% protection against the parent strain, but none gave heterologous protection against the A:L6 strains. Immunization with the thirteen D: L6 bacterins offered 60%–100% protection against the parent strain, and almost all D: L6 strains gave cross-protection. Discussion This study found that the cross-protectivity of serogroup A strains was poor, while serogroup D strains was effective, which provided some insights for P. multocida vaccine development.